Pertimbangan Hukum Hakim Menjatuhkan Sanksi Pidana Penjara Terhadap Penyalahgunaan Narkotika Tanpa Menerapkan Rehabilitasi Medis - Aswin Pramudita (Sebelas Maret University, 2017)
This study aims to determine the legal considerations imprisonment judge to impose sanctions against the abuse of drugs are in accordance Criminal Procedure Code and Law No. 35 Year 2009 on Narcotics and to implement the court ruling without medical rehabilitation of perpetrators of abuse of narcotics in accordance Supreme Court Circular No. 4 of 2010.This research is an applied prescriptive normative legal research. The approach used was statute and concept approaches. The law material used consisted of primary and secondary law source. Technique of collecting data used was document study, while technique of analyzing data used in this research was syllogism method with deductive thinking pattern.Legal considerations Surakarta District Court in examining and deciding the case of narcotics cases by case Number: 100 / Pid.Sus / 2015 / PN.SKT with sanctions of imprisonment in accordance with the Criminal Procedure Code and Law No. 35 Year 2009 on Narcotics. In accordance with the adoption of the law on justice and the rule of law. Surakarta District Court in deciding the case with No. 100 / Pid.Sus / 2015 / PN.SKT with cases of drug abuse which penalize without applying medical rehabilitation is not in accordance with the adoption of laws or in this case are not in accordance with SEMA No. 4 2010 on